TEACHING ENGLISH WITH AN INTERNET-BASED NATURE OF GOOGLE DOCS TO IMPROVE STUDENTS’ CRITICAL THINKING - Wahyuni, Erly (International Journal of Education, 2018)
One of the 4C skills required by the students in today’s global community is critical thinking. Critical thinking skill is not a skill that can evolve by itself along with the development of human body. Accordingly, it requires creativity on teachers’ side. The teacher can consider strategies and methods that can enhance students’ thinking ability. One of the strategies used by the teacher in teaching language to enhance learners’ critical thinking is internet-based nature of Google docs, an online application that can enrich learning environment by transferring teaching instruments that are user-centered. The objectives of this study are to identify the learning activities designed by the teacher to develop critical thinking; and describe the activities that expose the skill and to know the students’ responses toward the activities of teaching English with Google docs. This study employed descriptive qualitative method. The subjects consisted of an English teacher and 24 senior high school students in Malang. The instruments used included observation and open-ended questionnaire. The result of the analysis indicates that the English teacher designed the learning activities consisting of three main parts:  a) pre-teaching  that focuses on the orientation and registration of students to use email or user account to access to Google App; b) during teaching which focuses on students’ engagement of remembering, understanding, applying, analyzing, evaluating, and creating; and c) post-teaching  which includes sharing and providing students with opportunities to receive immediate feedback on their work. Meanwhile, the learning activities to develop students’ critical thinking not only refer to the teaching of English skills and those of language components but also integrating literary texts with answering effective questions. The students have positive responses toward the activities and they feel comfortable using technology as a medium to learn. Furthermore, they expect technology to be used in classroom as they completely adopted it in their lives.Keywords: Teaching English; critical thinking; Google docs